Performance and failure modes of Si anodes patterned with thin-film Ni catalyst islands for water oxidation. Issue 5 (28th March 2018) - Sun, Ke; Ritzert, Nicole L.; John, Jimmy; Tan, Haiyan; Hale, William G.; Jiang, Jingjing; Moreno-Hernandez, Ivan; Papadantonakis, Kimberly M.; Moffat, Thomas P.; Brunschwig, Bruce S.; Lewis, Nathan S.
Abstract : Silicon photoanodes patterned with thin-film Ni catalyst islands exhibited stable sunlight-driven O2 evolution for over 240 h of continuous operation in 1.0 M KOH. Abstract : Silicon photoanodes patterned with thin-film Ni catalyst islands exhibited stable oxygen evolution for over 240 h of continuous operation in 1.0 mol L −1 KOH under simulated sunlight conditions. Buried-junction np + -Si(111) photoanodes with an 18.0% filling fraction of a square array of Ni microelectrodes, np + -Si(111)|NiμE18.0%, demonstrated performance equivalent to a Ni anode in series with a photovoltaic device having an open-circuit voltage of 538 ± 20 mV, a short-circuit current density of 20.4 ± 1.3 mA cm −2, and a photovoltaic efficiency of 6.7 ± 0.9%. For the np + -Si(111)|NiμE18.0% samples, the photocurrent density at the equilibrium potential for oxygen evolution was 12.7 ± 0.9 mA cm −2, yielding an ideal regenerative cell solar-to-oxygen conversion efficiency of 0.47 ± 0.07%. The photocurrent passed exclusively through the Ni catalyst islands to evolve O2 with nearly 100% faradaic efficiency, while a passivating, insulating surface layer of SiO x formed in situ on areas of the Si in direct contact with the electrolyte. The (photo)electrochemical behavior of Si electrodes patterned with varying areal filling fractions of Ni catalyst islands was also investigated. The stability and efficiency of the patterned-catalyst Si electrodes were affected by the filling fraction of the Ni catalyst, the orientation and dopant type of the substrates, and the measurement conditions. The electrochemical behavior at different stages of operation, including Ni catalyst activation, Si passivation, stable operation, and device failure, was affected by the dynamic processes of anodic formation and isotropic dissolution of SiO x on the exposed Si. Ex situ and operando microscopic and spectroscopic studies revealed that these processes were three-dimensional and spatially non-uniform across the surface of the substrate, and occurred near the active catalyst islands. The patterned catalyst/substrate electrodes serve as a model system for accelerated studies of failure mechanisms in photoanodes protected by multifunctional catalytic coatings or other hole-conductive thin-film coatings that contain defects.